Low thermal-conductivity and high thermal stable silica aerogel based on MTMS/Water-glass co-precursor prepared by freeze drying. (5th January 2017) - Pan, Yuelei; He, Song; Gong, Lunlun; Cheng, Xudong; Li, Congcong; Li, Zhi; Liu, Zhong; Zhang, Heping
Abstract: In this paper, hybrid silica aerogels were prepared by methltrimethoxysilane (MTMS) and water-glass co-precursor through two-step sol-gel process followed by freeze drying (FD). The characteristics of aerogels were strongly affected by the molar ratio of MTMS/Water-glass. When the molar ratio is 5.1, hybrid aerogel was obtained with good performances, such as low density (0.083 g/cm 3 ), high contact angle (155.1°) and low thermal conductivity (0.0226 W/m·K). The density, contact angle and thermal conductivity of aerogels based on co-precursor are still showing excellent thermal stability with the same performances after 550 °C heat-treatment. Graphical abstract: Highlights: Hybrid aerogel based on organic and in-organic silicon source was prepared. Hybrid aerogel was prepared under freezing drying. The hybrid aerogel shows high thermal stability and low thermal conductivity.